Pengaruh Komunikasi Pemasaran Terhadap Minat Konsumen (Studi Kasus Di PT Haruman Multi Artha) - Adinda Viona Aurelia; Anas Hidayat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The purpose of this study was to determine the effect of marketing communications which include advertising (advertising), sales promotion (sales promotion), public relations (public relations), direct marketing (direct marketing), personal selling (personal selling) on ​​purchase intention. This type of research is quantitative with customer respondents at PT. Haruman Multi Artha totaling 60 respondents selected using purposive sampling technique. Data analysis used linear regression analysis with the IBM SPSS Statistics 23 test tool. The results showed that the marketing communications of PT. Haruman Multi Artha with advertising indicators (advertising) an average score of 3.63 (good category), sales promotion (sales promotion) an average score of 3.24 (sufficient category), public relations (public relations) an average score of 3 .33 (enough category), direct marketing (direct marketing) an average score of 3.38 (enough category), personal selling (personal selling) an average score of 3.69 (good category). There is a positive and significant influence on marketing communications which includes advertising, sales promotion, public relations, direct marketing, personal selling on PT. Haruman Multi Artha. The contribution of marketing communication variables to the buying interest of PT. Haruman Multi Artha of 61.2%, while the remaining 38.80% is influenced by other factors outside of this study